LEARNING MODEL PICTURE AND PICTURE IN INCREASING STUDENT INTEREST - Mazrur Mazrur; Surawan Surawan; Endah Mustika Pertiwi (Proceeding International Seminar of Islamic Studies, 2023)
This research aims to describe the implementation of Picture and Picture learning models in Fikih subjects and to know the impact of the implementation of picture and picture learning models in increasing students' interest in Fikih subjects at MTs Raudhatul Jannah Palangka Raya. This study used a quasi-experimental design with a non-equivalent control group design. The instrument used in this study was a validated questionnaire and tested before being used in the study. While the sample in this study amounted to 51 class VII students at MTs Raudhatul Jannah Palangka Raya. As for the distribution of 26 students as the control class and 25 students as the experimental class. Furthermore, the data analysis used to test the hypothesis is to use the